Modificações pós-traducionais das histonas H3S10ph, H3K9ac e H4K12ac associadas às enzimas Aurora B e GCN5 em carcinoma de células escamosas bucal - Garcia Junior, Marcelo Augusto (2020)
Epigenetic studies around histone modifications and their enzymes are of the utmost importance, especially regarding oral squamous cell carcinoma. It comes to the fore as they are epigenetic modifications involved in tumor progression and development. Therefore, our study intended to evaluate the expression of H3S10ph, H3k9ac, and H4K12ac histone modifications and GCN5 and Aurora B enzymes, analyzing their importance on OSCC patients. Firstly, a sample composed of 90 patients diagnosed with OSCC was selected. Then, immunohistochemical staining with antibodies against H3S10ph, H3K9ac, H4K12ac, GCN5, and Aurora B was performed on their paraffin-embedded tissue samples. An association of the histone modifications and enzyme expression levels with clinicopathological factors was prepared, as well as a correlation test and survival analysis. All the histone modifications and enzymes showed nuclear expression in tumor cells. The following significant associations were found: high Aurora B, GCN5, H3S10ph, H3K9ac, and H4K12ac with location site; high GCN5 and H3k9ac expression with smoking; low GCN5 expression with relapse. Besides that, a positive correlation was found between Aurora B and H3S10ph; GCN5 and H3K9ac; H3K9ac and H3S10ph; Aurora B and GCN5. Our findings suggest that H3S10ph, H3K9ac, H4K12ac, Aurora B, and GCN5 may participate in OSCC development, but not on its progression.